Postoperative Cardiac Biomarker Release After Minimally Invasive AV-Valve Surgery with or without Cryoablation - Lee, Jang-Sun; Berberoglu, Dilara M.; Ismail, Majd; Schönburg, Markus; Choi, Yeong-Hoon; Liakopoulos, Oliver J. (The Thoracic and Cardiovascular Surgeon, 2025)
Concomitant cryoablation is routinely performed in patients with atrial fibrillation who undergo minimally invasive atrioventricular (AV) valve surgery. While biomarker thresholds for postoperative myocardial infarction (pMI) are established in coronary artery bypass surgery, no clear thresholds exist after concomitant cryoablation in endoscopic valve surgery. This study aimed to analyze the perioperative cardiac biomarker release patterns in this patient cohort and to evaluate the applicability of SCAI-defined pMI thresholds.We retrospectively analyzed patients who underwent endoscopic AV valve surgery from 2018 to 2024, comparing those with cryoablation (n = 165; mean age: 66.5 ± 9.5 years) to those without (n = 513; mean age: 62.4 ± 12.0 years). Perioperative creatine kinase–myocardial band (CK-MB) and troponin T (TnT) levels were measured before surgery, at 1 and 4 hours after surgery, and on postoperative day 1 (1POD). In-hospital outcomes were also assessed.Cryoablation significantly increased CK-MB (6.4 × ULN vs. 2.4 × ULN, p < 0.001) and TnT (257 × ULN vs. 80 × ULN, p < 0.001). Compared with SCAI pMI criteria (CK-MB > 10 × ULN; TnT > 70 × ULN), CK-MB remained below the threshold, while TnT exceeded it in most cases (p < 0.05). Despite these elevations, clinical pMI was rare (two cases vs. three cases). In-hospital mortality did not differ significantly between the groups (1.2% vs. 1.6%; p = 1.000).Cryoablation during minimally invasive AV valve surgery markedly increases postoperative cardiac biomarkers without higher clinical pMI rates. Procedure-specific biomarker thresholds and validation of SCAI criteria are essential for accurate diagnosis and patient management.
Keywords: minimally invasive mitral valve surgery; cryoablation; cardiac biomarkers